Implementing a stakeholder-driven community diffusion-informed intervention to create healthier, more equitable systems: a community case study in Greenville County, South Carolina - Calancie, Larissa; Fair, Melissa L.; Wills, Sally; Werner, Kelsey; Appel, Julia M.; Moore, Travis R.; Hennessy, Erin; Economos, Christina D. (Frontiers in Public Health, 2023)
This case study describes the application of a theory-informed, stakeholder-driven intervention with a group of 19 multi-sector stakeholders from an existing coalition to promote whole-of-community change that supports childhood obesity prevention. The intervention applied community-based system dynamics to design and implement activities that promoted insights into the systems driving childhood obesity prevalence and helped participants prioritize actions to influence those systems. This led to three new priority areas for the coalition: addressing food insecurity; building power among historically marginalized voices within the community; and supporting advocacy efforts to promote community-wide change beyond the coalition’s previous focus on organizational-level policy, systems and environment change. The intervention spurred the application of community-based system dynamics to other health issues and in partner organizations, which demonstrates paradigm shifts about how to address complex public health issues in the community.